Neurological commentary addressing the article titled "Guidance for switching from off-label antipsychotics to pimavanserin for Parkinson's disease psychosis: an expert consensus". (27th December 2018) - Hermanowicz, Neal
Abstract : Parkinson's disease psychosis (PDP) occurs commonly and can comprise the most troubling symptoms among the many that occur with this illness. Prior treatment options for PDP have been limited and unsatisfactory due to uneven efficacy data, burdensome monitoring, and lack of a specific FDA indication coupled with warnings of increased mortality. Pimavanserin, approved for the treatment of PDP by the FDA in 2016, overcomes some of these obstacles, with data proven efficacy and without the frequent monitoring required for clozapine. This presents an opportunity to transition patients with PDP to pimavanserin from older therapies. Black and colleagues provide their thoughtful recommendations on how to achieve this transition to pimavanserin while maintaining symptom control and minimizing disruptions that might occur with a medication change.